Use of Ammonium Sulfate in Soil Produced with Residual Ammonia Liquor from the Steel Industry and Residual Sulfuric Acid from Automotive Batteries in the Initial Development of Maize (Zea Mays L.) - Costa, Alexandre Sylvio Vieira da; Fonseca, Marcos Cordeiro (Electronic Journal "Fórum Ambiental da Alta Paulista", 2026)
Objective –This study aims to evaluate the technical feasibility of producing ammonium sulfate from industrial residues and to assess its agronomic performance as a nitrogen and sulphur fertiliser for maize cultivation.Methodology – The research adopted an experimental approach based on controlled pot trials. Ammonium sulfate was produced using residual sulphuric acid from automotive batteries and ammonia liquor from the steel industry. A second formulation was prepared using residual acid and commercial ammonia, while analytical-grade ammonium sulfate (P.A.) was used as a reference. Fertiliser solutions were applied to soil at nitrogen rates ranging from 20 to 120 kg N·ha⁻¹, followed by sowing of maize (Zea mays L.). Plant growth and biomass accumulation were subsequently evaluated.Originality/Relevance – The study addresses a relevant gap concerning the reuse of industrial residues for fertiliser production, contributing to discussions on reducing Brazil’s dependence on imported fertilisers. It advances knowledge on alternative nutrient sources aligned with circular economy principles.Results – Maize plants showed positive responses to all ammonium sulfate sources tested. However, higher application rates resulted in phytotoxic effects, particularly in aerial biomass, while root biomass was negatively affected even at lower nitrogen doses.Theoretical/Methodological Contributions – The findings contribute to the understanding of nutrient dynamics and toxicity thresholds associated with alternative ammonium sulfate sources, offering methodological insights for evaluating residue-derived fertilisers under controlled conditions.Social and Environmental Contributions – The proposed approach promotes the valorisation of industrial residues, potentially reducing environmental liabilities and contributing to more sustainable fertiliser supply chains. Additionally, it supports strategies aimed at enhancing agricultural sustainability and fostering a more resilient and autonomous agricultural input supply.
Keywords: Industrial residues; Soil fertility; Crop development; Alternative fertilisers